Obstetric ultrasound training programmes for midwives: A scoping review - Yasmin Casmod; Susan J. Armstrong (AOSIS, 2023)
Background: Antenatal care is essential for all expectant mothers and assists in reducing maternal mortality rates thus addressing the Sustainable Development Goal 3. Obstetric ultrasound complements antenatal care and is used in pregnancy to identify and monitor high-risk pregnancies. However, disparities exist and in low- and middle-income countries, ultrasound services are not readily available. This contributes to maternal and neonatal morbidity and mortality within these populations. Short ultrasound training programmes for midwives can be beneficial in alleviating some of the challenges experienced. Aim: The aim of this scoping review was to identify global ultrasound education programmes for midwives. Method: Articles containing suitable keywords were retrieved from databases suitable to nursing, education and ultrasound. Themes were developed based on the articles included in the review. Results: A total of 238 articles were identified, and after the duplicates and irrelevant studies were removed, 22 articles were included. Articles were analysed and discussed under the identified themes and categories. Conclusion: It is essential that sufficient training is provided to medical professionals performing obstetric ultrasound so that adequate and safe care is offered to expectant mothers. With the introduction of ultrasound in low-resource settings, the knowledge of safety and competencies required to operate the equipment necessitate adequate training. Developed programmes have been found to meet the demands of the ever-changing workforce and allow for midwives to perform focused obstetric ultrasound examinations. Contribution: This scoping review highlighted ultrasound training programmes for midwives and provided guidance on the development of future midwifery ultrasound training programmes.